Experimental investigation on triple concentric tube heat exchanger. (2022) - Kumar Sharma, Deepak; Das, Nikimoni; Kumar Singh, Sanjay; Murari Pandey, Krishna
Abstract: The main objective of this research paper is to evaluate the performance of triple concentric tube heat exchangers experimentally under steady-state conditions. Water is considered as the working fluid and is circulated through the inner tube, inner annulus, and outer annulus at different temperatures. For this purpose hot water, normal water, and intermediate temperature water are considered. The experiment has been performed in the laboratory of the Mechanical Engineering Department at BIT Sindri Dhanbad in India. The arrangement of a triple concentric tube is installed by using three tubes of different materials. Aluminium, Copper, and galvanized iron (G.I) are used to make an inner tube, inner annulus, and outer annulus respectively. The variation of fluid temperature along the length of the heat exchanger has been measured. Also, the variation of friction factor and Nusselt number with Reynolds number has been studied for different conditions. The best result of this experimental study has been found in counter-current arrangement (A2) and the value of the overall coefficient is 0.42.